Recent advances in Musa genetics, breeding and biotechnology - Ortíz, R.; Vuylsteke, D.R. (1996)
Banana(Musa spp. L.) breeding, aiming to develop pest resistant cultivars for the export trade, started about 75 years ago in the West Indies. However, all banana exported today are still farmers' selection from somatic mutants of the group of Cavendish, and have a very narrow genetic base. In the five past years, breeding programmes in sub-Saharan Africa, tropical America and Asia have developed, through conventional cross breeding and induced mutation or somaclonal variation, improved germplasm (desert and cooking banana, and plantains) for local consumption. Also, as a result of this breeding work, a new insight into the musa genome was gained and the genetics of most important morphological traits and resistance to pests were elucidated. With this new knowledge as well as with advances in cell biology and recombinant DNA techniques, it is hoped that in the years to come the banana export trade will be based on artificially bred cultivars. This review discusses the achievements in banana and plantain breeding, genetics and biotechnology from the early to the mid-1990s and the potential for futher genetic improvement of this crop.